Efeitos da angiotensina-(1-7) na toxicidade induzida por tratamento com doxorrubicina - Ribeiro, Joseanne Daniele Cezar (2018)
According to data from the National Cancer Institute José Alencar Gomes da Silva (INCA), in the biennium 2018-2019, for each year, a value of 600 thousand new cancer cases in Brazil is approaching. As therapeutic output to reach the important population number affected by this disease, there are antitumor antibiotics, antineoplastic agents where doxorubicin is inserted. Despite its effectiveness in fighting tumor cells, its use may cause adverse reactions such as cardiotoxicity. In pharmacological approaches, a substance that has potential in the area of cardiac protection is Angiotensin- (1-7), an endogenous heptapeptide that participates in the renin-angiotensin system. Therefore, the objective of this study was to investigate the effects of Angiotensin- (17) on the prevention and treatment of toxicity caused by Doxorubicin. In this study 35 adult Wistar rats (Rattus novergicus), weighing 160-278g, were used from the Biotério Prof. Thomas George of the Federal University of Paraíba. The animals went through a cycle of six weeks of experimentation, being divided into 6 groups: Control Saline, Control Ang- (1-7), Control doxorubicin, Preventive 1 and 2, and Treatment group. The animals were submitted to 3 echocardiographic evaluations during these weeks and at the end of the treatment were euthanized, with subsequent evaluation of the following organs weight: heart, lung, kidneys (L and R), spleen and liver, besides morphological analysis macroscopic examination of the animals organism (with photographic record execution). In the evaluation of survival, the Control Saline Solution group and Control Ang-(1-7) arrived at the end of the experiment with all live animals, in opposition to the treatment groups that received Ang-(1-7) and doxorubicin. In the Doxo and Treatment control groups there was a decrease in the body mass value of the animals, besides characteristics such as apathy and dehydration and diarrheal feces with mucus. The control group Saline Control in the evaluation of the necropsy presented a morphology with hemorrhagic foci in the lungs, white patches in both kidneys and only one of the rats of this group was able to observe macroscopic morphological normality. The control Ang-(1-7) group presented normal morphological characteristics. The animals in the groups receiving doxorubicin had characteristic stiffness in the organs, especially in the liver, besides the accumulation of fluid in the peritoneal cavity, hemorrhagic foci in the lungs and in one animal there was an increase in the seminal vesicles and gallbladder , it is noteworthy that in the groups in which Ang- (1-7) interaction with doxorubicin also showed an increase in lung volume. Regarding left ventricular function, the animals showed a similar profile between the treatment groups and about the structure there was a decrease in the diastolic diameter, interventricular septum and posterior wall of the left ventricle compared to the Control group. The control group Ang- (1-7) behaved the same as the Control group, showing that Ang- (1-7), when administered alone, does not promote changes in the organs. Isolated heart mass showed a reduction in the groups Control doxorubicin, Preventive 1 and Treatment, but in relation to the body mass, we verified that the proportion was not altered between the groups. The isolated lung mass was altered in the Preventive 1 and Preventive 2 groups and in the organ mass/body mass ratio of the animal, this increase in lung volume can also be observed in the Control doxorubicin and Treatment groups. The spleen of the animals presented alteration only in Preventive 2 group. We did not find any difference in the kidney mass (L and R) between the treatment groups, but we observed that if the organ mass/body mass ratio was observed, there was an increase in the groups that received only doxorubicin at the beginning of the experiment. Finally, the liver mass of the animals did not show any difference between the groups when observed alone, but when considered the body mass of the animal, the groups Control doxorubicin, Preventive 1 and Treatment showed an important difference of the Control Saline group. In view of the results it was not possible to analyze the prevention of cardiotoxicity by Ang- (1-7), and when administered in combination with doxorubicin the effects were too deleterious.